Experimental and Numerical Study of Basalt FRP Strip Strengthened RC Slabs under Impact Loads - Chen, Wensu; Pham, Thong; Elchalakani, M.; Li, H.; Hao, Hong; Chen, L. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2020)
Basalt fiber-reinforced polymer (BFRP) has been applied for strengthening concrete structures. However, studies on reinforced concrete (RC) slabs strengthened by BFRP strips under impact loads are limited in open literature. This study investigates the efficiency of using BFRP strips with various strengthening layouts and anchoring schemes on the impact resistance of RC slabs. A total of 11 two-way square slabs were prepared and tested, including one reference specimen without strengthening and ten slabs strengthened with BFRP strips and/or anchors. The RC slabs were impacted by a drop weight with increasing height until slab failure. The observed failure modes include punching shear failure, BFRP sheet debonding and reinforcement fracture. The failure modes and the effects of using various strengthening schemes on the impact resistant capacity of RC slabs were examined. The quantitative measurements, such as impact velocity, indentation depth and diameter, were compared and discussed. In addition, numerical studies were carried out by using LS-DYNA to simulate the impact tests of RC slabs with and without BFRP strengthening. With the calibrated numerical model, the impact behavior of slabs with various dimensions and strengthening layouts under different impact intensities can be predicted with good accuracy.